Santri Lelana dan Relasi Tanda dalam Naskah Sejarah Syarif Hidayatullah Koleksi Masyarakat Indramayu Jawa Barat - Mashuri, Mashuri (Manuskripta, 2024)
This study investigates the spiritual journey of Syarif Hidayatullah, a prominent figure in Javanese Sufism, as depicted in the manuscript Sejarah Syarif Hidayatullah (DS 0021 00001). Employing a combination of philological and cultural semiotic methodologies, this research analyzes the manuscript, which dates back to 1973 and resides in the private collection of Ki Lebe Ibrohim in Indramayu, West Java. The narrative, characteristic of the santri lelana genre, portrays Syarif Hidayatullah's spiritual path as a three-stage progression: the pursuit of Muhammad's light, the quest for Syahadat Sejati (True Testimony of Faith), and the manifestation of this attained truth. Each stage exhibits unique trajectories, dimensions, and accomplishments. Furthermore, the analysis reveals a rich tapestry of signs and symbols embedded within Syarif Hidayatullah's journey, reflecting the interplay of Javanese or Sundanese cultural elements and Sufi principles. === Penelitian ini mendalami perjalanan spiritual Syarif Hidayatullah, tokoh penting dalam sufisme Jawa, sebagaimana digambarkan dalam manuskrip Sejarah Syarif Hidayatullah (DS 0021 00001). Menggunakan pendekatan filologis dan semiotika budaya, penelitian ini menganalisis manuskrip yang berasal dari tahun 1973 dan tersimpan dalam koleksi pribadi Ki Lebe Ibrohim di Indramayu, Jawa Barat. Narasi dalam manuskrip, yang khas dari genre "santri lelana", menggambarkan perjalanan spiritual Syarif Hidayatullah melalui tiga tahapan: pencarian cahaya Muhammad, pencarian "Syahadat Sejati", dan manifestasi kebenaran yang diperoleh. Setiap tahapan memiliki karakteristik, dimensi, dan pencapaian yang unik. Lebih lanjut, analisis mengungkapkan kekayaan simbol-simbol yang tertanam dalam perjalanan Syarif Hidayatullah, mencerminkan interaksi antara unsur-unsur budaya Jawa atau Sunda dengan prinsip-prinsip Sufi